The impact of the covid-19 pandemic on coverage of basic immunization in Jayapura city public health centers - Kismiyati; Sunarti (Science Midwifery, 2023)
The government has declared Coronavirus Disease 2019 (COVID-19) as a non-natural disaster in the form of an outbreak/pandemic, this determination is followed by efforts to prevent the spread of the corona virus. This condition also affects the schedule and procedures for immunization services both at posyandu, puskesmas and other health facilities including the private sector. The survey results showed that almost 84% of health facilities reported that immunization services experienced significant disruption due to the COVID-19 outbreak (Ministry of Health, UNICEF 2020). Objective: To determine the impact of COVID-19 on basic immunization coverage at health centers in Jayapura City. This research method is a combination of quantitative and qualitative methods. The sample is all health centers in Jayapura City. The research location is in Jayapura City. Time from June to October 2020. The independent variables are the COVID-19 pandemic and the dependent variables are basic immunization coverage and immunization service policies. The instruments used were questionnaires and interview guidelines. Data analysis was carried out in a bivariate manner for quantitative data and qualitative analysis. Research Results Immunization Coverage before and during the pandemic decreased by a difference of 898. The average immunization coverage before the pandemic was 334.5 and during the pandemic the value decreased by an average of 222.5. Based on the results of the paired t test, it was found that the value of p = 0.003 (<0.005) where there was a significant difference in the coverage of immunization before and during the Covid-19 pandemic at public health centers in Jayapura. Conclusion The Covid-19 pandemic has had an impact on decreasing immunization coverage at the Public Health Center in Jayapura City.